Biomimetic Iodofunctionalization of Aromatic and Heteroaromatic Compounds Catalyzed by Selenium Tetrachloride - Rocha, Beatriz C. O.; Perecim, Givago P.; Raminelli, Cristiano (SynOpen, 2019)
A biomimetic iodofunctionalization of aromatic and heteroaromatic compounds has been developed using NaI as a source of iodine and 30% H2O2 as a mild oxidant, as well as SeCl4 as a commercially available catalyst in water without a co-solvent. The method affords iodinated compounds in isolated yields of 37 to 99%. The catalytic system has potential for the bromination of aromatic substrates.
Keywords: biomimetic synthesis; iodofunctionalization; selenium catalysis; iodination; aqueous reaction